TSLP-induced placental DC activation and IL-10(+) NK cell expansion comparative study based on BALB/c x C57BL/6 and NOD/SCID x C57BL/6 pregnant models - Lin, Yi (Clinical immunology (Orlando, Fla.), 2008)
Thymic stromal lymphopoietin (TSLP)-TSLP receptor (TSLP-R) interactions activate CD11c(+) dendritic cells (DCs) and increase epithelial cell Th2-type cytokine production. We detected intracellular TSLP expression on CK7(+) trophoblast cells and TSLP-R expression on placental DCs from pregnant BALB/cxC57BL/6 and NOD/SCIDxC57BL/6 mice on gestational day 12.5. Murine recombinant TSLP activated DCs from BALB/c mice, with increased CD80 and CD83 expressions; TSLP-activated DCs induced IL-10-producing NK cell expansion. This was abrogated by anti-TSLP Ab or by culturing CD49b(+) NK cells alone. No TSLP-DC-induced IL-10(+)CD49b(+) cell expansion occurred when DCs and CD49b(+) cells were cultured separately. Although TSLP-induced DC activation occurred in NOD/SCID mice, the IL-10(+) NK cell percentage was unchanged. CK7(+) trophoblast cells may activate placental DCs via a TSLP-TSLP-R interaction and induce DC-dependent placental NK cell IL-10 production. TSLP-DC and NK cell contact appears necessary for IL-10(+)CD49b(+) cell expansion. Placental NK cells from NOD/SCIDxC57BL/6 mice appear less sensitive to TSLP-DC induction